Pengaruh Kualitas Produk, Promosi, dan Citra Merek Terhadap Keputusan Pembelian Air Minum Le Minerale di Kota Depok, Jawa Barat. - Iswiyanti, Agus Sri; Sylviani, Delia; Rachmat, Stanty Aufia (Jurnal USAHA, 2025)
This study aims to determine and examine the ways in which marketing, product quality, and brand perception affect consumers' decisions to purchase Le Minerale drinking water in Depok, West Java. The main in this investigation, quantitative data was used. Examples of pengujian approaches include validity, reliability, multiple linear regression analysis, Classic tests, and hypotheses like partial T and F. Either alongside the Tes Coefficient Determination (R Square) or in addition to it. To achieve this research goal, a Google Forms-created questionnaire instrument is used to collect data from 110 participants.To provide the facts in an understandable way, all 30 responders are analysed. This study's approach blends intentional sampling with non-probability sampling.    The SPSS version 27 is used. The study's findings demonstrate that brand image, promotion, and product quality significantly influence consumers' decisions to buy, both separately and in combination. buy Le Minerale drinking water in Depok City, West Java.Keywords: Product Quality, Marketing, Brand Image, and Intentions to Buy